Effect of N-doping, exfoliation, defect-inducing of Ni-Fe layered double hydroxide (Ni-Fe LDH) nanosheets on catalytic hydrogen storage of N-ethylcarbazole over Ru/Ni-Fe LDH. (15th December 2021) - Shi, Jiaming; Liu, Xiaoran; Bai, Xuefeng
Graphical abstract: Highlights: Highly active and stable Ru/Ni-Fe LDH for NEC hydrogenation is prepared. Reduction, N-doping, exfoliation and defects are simultaneously realized by plasma. Synergy between Ru and N-doped LDH with defects improves catalytic performance. The complexation of doped nitrogen with Ru improves the catalytic stability. Abstract: Ultrafine Ru nanoparticles (RuNPs) supported on N-doped exfoliated Ni-Fe layered double hydroxide (LDH) nanosheets (Ru/Ni-Fe LDH) are prepared by nitrogen glow discharge plasma without adding any chemical stabilizers or reducing agents. The Ru/Ni-Fe LDHs were characterized by FT-IR, XPS, XRD, AFM, TEM, SEM and N2 physical adsorption–desorption analysis methods. The results show that the glow discharge plasma is not only able to reduce Ru 3+ to Ru, but can also exfoliate Ni-Fe LDH into nanosheets and produce defects and dope N into the layered structure of Ni-Fe LDH. RuNPs with an average particle size of 1.81 nm were successfully obtained and well dispersed on the surface of N-doped exfoliated Ni-Fe LDH nanosheets. The experimental results from the catalytic hydrogenation of N-ethylcarbazole (NEC) over Ru/Ni-Fe LDH show that the NEC conversion is 100%, the dodecahydro-N-ethylcarbazole (12H-NEC) selectivity is 97.43%, and the mass hydrogen storage capacity is 5.74 wt% under the reaction temperature and pressure of 120 °C and 6 MPa for 80 min. The apparent activation energy is 44.86 kJ/mol.